The therapeutic alliance in different mental disorders: A comparison of patients with depression, somatoform, and eating disorders. (12th May 2017) - Mander, Johannes; Neubauer, Andreas B.; Schlarb, Angelika; Teufel, Martin; Bents, Hinrich; Hautzinger, Martin; Zipfel, Stephan; Wittorf, Andreas; Sammet, Isa
Abstract : Objective: The therapeutic alliance is intensively investigated in psychotherapy research. However, there is scarce research on the role of the specific diagnosis of the patient in the formation of the therapeutic alliance. Hence, the aim of this study was to address this research gap by comparing the alliance in different mental disorders. Design: Our sample comprised 348 patients (mean age = 40 years; 68% female; 133 patients with depression, 122 patients with somatoform disorders, and 93 patients with eating disorders). Methods: Patients completed the Working Alliance Inventory and measures of therapeutic outcome in early, middle, and late stages of inpatient psychotherapy. We applied multivariate multilevel models to address the nested data structure. Results: All three disorder groups experienced positive alliances that increased across the course of therapy and showed similar alliance–outcome relations that were of comparable strengths as in current meta‐analyses. However, we found perspective incongruence of alliance ratings from patient and therapist in the three disorder groups. Conclusions: Our results generally indicate that the working alliance is of importance irrespective of the specific mental disorder. Perspective incongruence feedback of working alliance experiences could help to strengthen coordination between patient and therapist and thereby improve the therapeutic process. Further implications of these findings are discussed. Practitioner points: We found no differences in the strengths of alliance ratings and alliance–outcome associations in depressive, somatoform, and eating disorder patients. This indicates that the working alliance is of general clinical importance irrespective of the disorder group and should be a central target in all therapies. We found perspective incongruence in alliance ratings between patient and therapist in all three disorder groups. Perspective incongruence feedback of working alliance experiences could help to strengthen coordination between patient and therapist and thereby improve the therapeutic process.